2020
DOI: 10.1101/2020.01.24.919001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macrophages Promote Aortic Valve Cell Calcification Through STAT3 Splicing

Abstract: ObjectiveMacrophages have been described in calcific aortic valve disease, but it is unclear if they promote or counteract calcification. We aimed to determine how macrophages are involved in calcification using the Notch1 +/model of calcific aortic valve disease. Approach and ResultsMacrophages in wild-type and Notch1 +/murine aortic valves were characterized by flow cytometry. Macrophages in Notch1 +/aortic valves had increased expression of MHCII. We then used bone marrow transplants to test if differences … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…6). Immune cell recruitment plays a key role in other 5-HT 2B -mediated fibrotic disease and has been shown to contribute to the Notch1 +/model of CAVD, suggesting it may be involved here (23,33,34). This may also indicate a phenotype arising from cells other than myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Immune cell recruitment plays a key role in other 5-HT 2B -mediated fibrotic disease and has been shown to contribute to the Notch1 +/model of CAVD, suggesting it may be involved here (23,33,34). This may also indicate a phenotype arising from cells other than myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical and basic research findings led us to hypothesize that 5-HT 2B may be a novel target for pharmacological treatment of CAVD. Therefore, we evaluated the impact of both genetic and pharmacological ablation of 5-HT 2B in the well-established Notch1 +/mouse model of CAVD, based on the heritable form in patients with NOTCH1 mutations (19)(20)(21)(22)(23). Briefly, we found that genetic ablation mitigated CAVD phenotypes, while pharmacological targeting was not efficacious.…”
Section: Introductionmentioning
confidence: 99%